Variations in the prostate of Molossus molossus during the processes of testicular maturation, regression, and recrudescence: Morphophysiology and hormonal control - Soares, Emília M [UNESP]; Ferraz, Juliana F; Santiago, Cornélio S; Venâncio, Larissa P R; Perez, Ana Paula S; Macedo-Junior, Arlindo G; Taboga, Sebastião R [UNESP]; Beguelini, Mateus R (Elsevier, 2025)
Molossus molossus (Chiroptera: Molossidae) is a species of molossid bat whose males show a period of total testicular regression during the reproductive cycle in western Bahia, Brazil. Testicular regression directly affects the prostate due to the androgen dependence of this organ. During regression, there is a decrease in androgen levels, which leads to morphophysiological changes in the gland. The aim of this study was to analyze the regulation and signaling of the prostate of M. molossus throughout the processes of testicular maturation, regression, and recrudescence. The bat's prostate complex in four phases (juvenile, active adult, regressing adult, and recrudescent adult) was analyzed using histological, morphometric, and immunohistochemical procedures to characterize its variations, analyze its hormonal regulation, and assess whether the prostate is affected by the processes of testicular regression and recrudescence. Blood was subjected to hormone dosage for testosterone and estradiol. The processes of total testicular regression and recrudescence directly affect the physiology of the prostate of M. molossus, but with a delay in the prostatic response, due to the delay in the rise in testosterone concentration. The prostate in this species seems to be regulated by the interaction between the serum hormone levels (testosterone and estradiol) and their specific receptors (androgen receptor and estrogen receptors α and β), which regulates prostatic cell proliferation and apoptosis.